A 1.5-V 45-mW direct-conversion WCDMA receiver IC in 0.13-μm CMOS. - Rogin, J. (IEEE Journal of solid state circuits)
A 2-GHz direct-conversion receiver for wide-band code division multiple access (WCDMA) is presented. It includes two low-noise amplifiers (LNAs), an I/Q demodulator, and two sixth-order baseband channel select filters with programmable gain. Quadrature local oscillator (LO) signals are generated on chip in a frequency divider flip-flop. An external interstage filter between the LNAs rejects transmitter leakage to relax demodulator linearity requirements. A low-voltage demodulator topology improves linearity as well as demodulator output pole accuracy. The active-RC baseband filter uses a programmable servo loop for offset compensation and provides an adjacent channel rejection of 39 dB. Programmable gain over 71-dB range in 1-dB steps is merged with the filter to maximize dynamic range. An automatic on-chip frequency calibration scheme provides better than 1.5% corner frequency accuracy. The receiver is integrated in a 0.13-μm CMOS process with metal-insulator-metal (MIM) capacitors. Measured receiver performance includes a 6.5-dB noise figure, IIP2 of +27 dBm, and IIP3 of -8.6 dBm. Power consumption is 45 mW.